2013
DOI: 10.1007/s10532-013-9664-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of an attached-growth process for the on-site bioremediation of an aquifer polluted by chlorinated solvents

Abstract: A procedure for the design of an aerobic cometabolic process for the on-site degradation of chlorinated solvents in a packed bed reactor was developed using groundwater from an aquifer contaminated by trichloroethylene (TCE) and 1,1,2,2-tetrachloroethane (TeCA). The work led to the selection of butane among five tested growth substrates, and to the development and characterization from the site's indigenous biomass of a suspended-cell consortium capable to degrade TCE (first order constant: 96 L gprotein(-1) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Complete anaerobic biodegradation and detoxification of TeCA was described with consortia containing multiple dehalorespiring microorganisms whereas pure strains were reported to be able to degrade TeCA incompletely . On the other hand, in recent years a limited number of studies demonstrated the possibility to biodegrade TeCA via aerobic co‐metabolism using mixed cultures . Further, some studies have characterized both aerobic and anaerobic microbial communities able to degrade TeCA for bioaugmentation purposes in the light of a bioremediation strategy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete anaerobic biodegradation and detoxification of TeCA was described with consortia containing multiple dehalorespiring microorganisms whereas pure strains were reported to be able to degrade TeCA incompletely . On the other hand, in recent years a limited number of studies demonstrated the possibility to biodegrade TeCA via aerobic co‐metabolism using mixed cultures . Further, some studies have characterized both aerobic and anaerobic microbial communities able to degrade TeCA for bioaugmentation purposes in the light of a bioremediation strategy …”
Section: Introductionmentioning
confidence: 99%
“…Methane, toluene, phenol, ammonia, propane and butane have been effectively utilized as growth substrates for bacterial CAH aerobic co‐metabolism. In particular, propane‐utilizers have demonstrated the ability to oxidize various CAHs such as vinyl chloride, 1,1,2‐trichloroethane, chloroform, trichloroethylene . Indeed, it was shown that propane induces the synthesis of a monooxygenase that is responsible for one or more CAHs transformation due to its relaxed substrate range .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its potential carcinogenic and mutagenic effects, the USEPA has set the Maximum Contaminant Levels (MCLs) for TCE in drinking water at a low concentration of 5 µg L −1 . Methods that have been used to remove or degrade TCE in groundwater include microbial transformation [8-12] and chemical oxidation or reduction [13-16]. Electrochemical methods are also widely investigated, due to the advantage of in situ formation and control of oxidizing and/or reducing conditions [17-24].…”
Section: Introductionmentioning
confidence: 99%
“…Equipment is commercially available and engineering design requirements are generally well defined for building biofilm reactors. Numerous laboratory scale studies have examined the anaerobic treatment of individual chlorinated ethenes and ethanes in upflow anaerobic sludge blanket (Basu and Asolekar 2012a, b, c;Hwu and Lu 2008;Sponza 2003, Basu andGupta 2010;Liu et al 2003;Prakash and Gupta 2000), aerobic soil slurry (Frascari et al 2010), anaerobic fixed-bed (Wild et al 1995), aerobic packed-bed (Frascari et al 2014), anaerobic packed bed (Mijaylova-Nacheva and Canui-Chuil 2006), aerobic fluidized-bed (Segar et al 1997) and aerobic suspended growth bioreactors (Frascari et al 2010).…”
Section: Introductionmentioning
confidence: 99%